2011
DOI: 10.1530/eje-10-0967
|View full text |Cite
|
Sign up to set email alerts
|

VEGFR1 expression is related to lymph node metastasis and serum VEGF may be a marker of progression in the follow-up of patients with differentiated thyroid carcinoma

Abstract: ObjectiveVascular endothelial growth factor (VEGF) and VEGF receptor 1 (VEGFR1) are known to be related to thyroid tumorigenesis. The aim of the study was to examine the expressions and serum levels of VEGF, VEGFR1, IGF1, and IGF1 receptor (IGF1R) in patients with differentiated thyroid carcinoma (DTC) compared with patients with nodular goiter (NG).MethodsWe examined 39 patients with DTC who had a clinical history of at least 2 years and compared them with 25 patients who had a pathological diagnosis of NG af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 47 publications
1
28
0
Order By: Relevance
“…Vascularization is an important feature of tumor growth that might contribute to the growth and progression of thyroid nodules and VEGF is one of the most powerful angiogenesis stimulators (4,29). High expression of VEGF in thyroid cancer was found to be correlated with advanced tumor stage, lymph node metastasis, and increased risk of recurrence (5)(6)(7). Therefore, VEGF inhibitors are approved for the treatment of advanced thyroid cancers (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vascularization is an important feature of tumor growth that might contribute to the growth and progression of thyroid nodules and VEGF is one of the most powerful angiogenesis stimulators (4,29). High expression of VEGF in thyroid cancer was found to be correlated with advanced tumor stage, lymph node metastasis, and increased risk of recurrence (5)(6)(7). Therefore, VEGF inhibitors are approved for the treatment of advanced thyroid cancers (30).…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF) is a critical regulator of angiogenesis and is involved in tumor development. VEGF expression was found to be associated with lymph node metastasis, advanced tumor stage, and increased recurrence risk in malignant thyroid cancers (5)(6)(7). Research investigating the role of VEGF in benign thyroid disorders yielded controversial results.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, increased serum VEGF levels in PTC patients returned to normal after therapy . Moreover, serum VEGF may be a marker of progression in the follow‐up of patients with PTC …”
Section: Discussionmentioning
confidence: 95%
“…The microvascular density in thyroid cancer tissue is increased when compared to normal thyroid tissue . Accumulating data have shown that increased VEGF expression promotes cancer cell growth, subsequent lymph node metastasis, local invasion, and distant metastasis, whereas the inhibition of VEGF signaling results in suppression of the tumor growth . In addition, preoperative serum VEGF levels were shown to be elevated in PTC patients and correlated with different clinicopathological features corresponding to their expected biological effects .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation